Effects of Acute and Chronic Heavy Metal (Cu, Cd, and Zn) Exposure on Sea Cucumbers (Apostichopus japonicus). (12th June 2016) - Li, Li; Tian, Xiangli; Yu, Xiao; Dong, Shuanglin
Abstract : Acute and chronic toxicity tests were conducted with sea cucumber ( Apostichopus japonicus ) exposed to heavy metals. Acute toxicity values (96 h LC50) were 2.697, 0.133, and 1.574 mg L −1 for Zn, Cu, and Cd, respectively, and were ranked in order of toxicity: Cu > Cd > Zn. Under chronic metal exposure the specific growth rates of sea cucumbers decreased with the increase of metal concentration for all the three metals. After acute metal exposure, the oxygen consumption rate (OCR) decreased. The OCRs in all groups were significantly different than control (P < 0.05 ) except in the group treated with 1.00 mg L −1 Zn (P < 0.05 ), where the increase of OCR was observed. The OCRs in groups chronically exposed to metals were significantly lower than that in the control group (P < 0.05 ). The activity of both pyruvate kinase (PK) and hexokinase (HK) in sea cucumbers followed: respiratory tree > muscle > intestine in natural sea water. After chronic Zn, Cu, and Cd exposure, the change pattern of HK and PK in respiratory tree, muscle, and intestine varied slightly. However, the activity of the enzyme showed a general trend of increase and then decrease and the higher the exposure concentration was, the earlier the highest point of enzyme activity was obtained.